PERIPHERAL MECHANISMS CONTRIBUTING TO OSTEOARTHRITIS PAIN - Syx, Delfien (Curr Rheumatol Rep, 2018)
PURPOSE OF REVIEW: Osteoarthritis (OA) is the most common form of arthritis and a major source of pain and disability worldwide. OA-associated pain is usually refractory to classically used analgesics, and disease-modifying therapies are still lacking. Therefore, a better understanding of mechanisms and mediators contributing to the generation and maintenance of OA pain is critical for the development of efficient and safe pain-relieving therapies. RECENT FINDINGS: Both peripheral and central mechanisms contribute to OA pain. Clinical evidence suggests that a strong peripheral nociceptive drive from the affected joint maintains pain and central sensitization associated with OA. Mediators present in the OA joint, including nerve growth factor, chemokines, cytokines, and inflammatory cells can contribute to sensitization. Furthermore, structural alterations in joint innervation and nerve damage occur in the course of OA. SUMMARY: Several interrelated pathological processes, including joint damage, structural reorganization of joint afferents, low-grade inflammation, neuroplasticity and nerve damage all contribute to the pain observed in OA. It can be anticipated that elucidating exactly how these mechanisms are operational in the course of progressive OA may lead to the identification of novel targets for intervention.